An optimal PMU placement method against measurement loss and branch outage - Chawasak Rakpenthai (2018)
This paper presents a new method for an optimal measurement placement of phasor measurement units (PMUs) for power system state estimation. The proposed method considers two types of contingency conditions, i.e. single measurement loss and single branch outage, in order to obtain a reliable measurement system. Firstly, the minimum condition number of the normalized measurement matrix Is used as the criteria in conjunction with the sequential elimination approach to obtain a completely determined condition. Next, a sequential addition approach is used to search for necessary candidates for single measurement loss and single branch outage conditions. These redundant measurements are optimized by the binary integer programming. Finally, in order to minimize the number of PMU placement sites, a heuristic technique to re-arrange measurement positions is also proposed. Numerical results on the IEEE test systems are demonstrated. ©2007 IEEE.